Sistemática da tribo Heroini Kullander, 1998 (Perciformes, Cichlidae). - Graça, Weferson Júnio da (2008)
The Cichlidae family comprises about 1600 valid species, being a one of the larger groups of vertebrates. They are distributed in Africa, South and Central America, Southeastern of North America (South of Texas and México), Madagascar, India, Sri Lanka, Syria, Israel and Irã. The Heroini tribe is the second most speciose tribe of Cichlidae in the Neotropical region, with more than 140 species belonging to 28 valid genera. Their greatest diversity occurs in Centro-America with 100 valid species. This tribe is distributed from South of Buenos Aires, Argentina, Australoheros Rícan & Kullander, to Bravo-Grande rivers basin, USA, Herichthys Baird & Girard. The phylogenetic analysis using 141 morphological characters of the 95 taxa, 55 species of the 28 valid genus of Heroini, resulted in the monophyletic Heroini tribe, diagnosed by three derived features: lacking contact between and the vomer, single palato-ethmoid articulation, and four or more spines in the anal-fin. Heroini tribe is the sister-group of Cichlasomatini tribe, the genera Hoplarchus + Hypselecara were given as the most basal of Heroini, and the sister group of remaining Heroini. The South American genera Australoheros, Caquetaia and Heroina are sistergroup of some Central American genera. Comments about biogeographic patterns of Heroini tribe are provided. Additionally, three new genera are proposed for encompassing currently assigned to 'Cichlasoma'